Interaction between SIRT1 and non-coding RNAs in different disorders - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Hussen, Bashdar Mahmud; Poornajaf, Yadollah; Taheri, Mohammad; Sharifi, Guive (Frontiers in Genetics, 2023)
SIRT1 is a member of the sirtuin family functioning in the process of removal of acetyl groups from different proteins. This protein has several biological functions and is involved in the pathogenesis of metabolic diseases, malignancy, aging, neurodegenerative disorders and inflammation. Several long non-coding RNAs (lncRNAs), microRNAs (miRNAs) and circular RNAs (circRNAs) have been found to interact with SIRT1. These interactions have been assessed in the contexts of sepsis, cardiomyopathy, heart failure, non-alcoholic fatty liver disease, chronic hepatitis, cardiac fibrosis, myocardial ischemia/reperfusion injury, diabetes, ischemic stroke, immune-related disorders and cancers. Notably, SIRT1-interacting non-coding RNAs have been found to interact with each other. Several circRNA/miRNA and lncRNA/miRNA pairs that interact with SIRT1 have been identified. These axes are potential targets for design of novel therapies for different disorders. In the current review, we summarize the interactions between three classes of non-coding RNAs and SIRT1.